(untitled) (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2024)
Background: Osteoporosis and vitamin D deficiency (VDD) are growing concerns for the elderly population, especially postmenopausal women worldwide. The association between osteoporosis and VDD among Bangladeshi postmenopausal women was not adequately evaluated. Objective: To assess the association between VDD, intact parathyroid hormone (iPTH) status, and bone mineral density (BMD) status among postmenopausal Bangladeshi women. Methods: This single-center, cross-sectional study included 60 postmenopausal women. A pre-designed case record form was used to record baseline demographic variables. BMD was assessed using dual-energy X-ray absorptiometry on eligible patients who met the inclusion and exclusion criteria, where T-scores indicating normal (> -1), osteopenia (-1 to -2.5), or osteoporosis (< -2.5) based on lumbar spine (LS) and femoral neck (FN) measurements. Vitamin D was categorized as deficient (<20 ng/mL), insufficient (VDI: 20–29 ng/mL), or sufficient (≥30 ng/mL) based on serum 25(OH)D levels. Vitamin D and iPTH were measured by chemiluminescence immunoassay. Results: Among 60 postmenopausal women, 43.3% had osteoporosis and 56.7% had no osteoporosis. VDD, insufficiency, and sufficiency were present in 50%, 35%, and 15% respectively in the study participants. Serum iPTH was higher in 20.0% of the study participants. Vitamin D levels were lower in women with osteoporosis than those without [15.6±5.5 vs. 20.6±8.9, p <0.001]. Serum iPTH negatively and moderately correlated with 25(OH)D and LS-BMD [both: r=-0.4, p=0.001] but not with FN-BMD. In multivariate regression analysis, only serum iPTH [B=0.4, p=0.001] and vitamin D insufficiency [B= 0.5, p=0.015] had a predictive association with LS-BMD. Conclusion: Both VDD and osteoporosis, are common in postmenopausal Bangladeshi women. Low vitamin D levels can play a role in developing osteoporosis by increasing bone remodeling as an effect of raised iPTH. J Assoc Clin Endocrinol Diabetol Bangladesh, July 2024;3(2): 47-52